Assistance in an outpatient burn Treatment Centre in Southern Brazil: profile and opinion of users - Iakmiu Camargo Cabulon, Elisana Agatha; Trevisan Martins, Julia; do Carmo Cruz Robazzi, Maria Lucia; Maciel Cardelli, Alexandrina Aparecida (O Mundo da Saúde, 2015)
Characterize the sociodemographic profile and history of users of outpatient morbidity Burn Treatment Centre of Londrina (BTC) and know their opinion about the service. This is a descriptive study of qualitative and quantitative approach. The population consisted of all individuals who were being treated in the outpatient BTC from June 2012 to January 2013. Data were collected through a questionnaire, medical records and conducting exploratory interview on the user opinion about the service. The interview answers were transcribed and subjected to Content Analysis method of Bardin. Quantita- tive data were analyzed by descriptive analysis with Statistical Package for the Social Sciences (SPSS).The total amount was 105 participants, the majority (66.0%) between 20 and 49 years old, with 51.0 % of the population had low education, and 74.0 % had burns on the trunk. The user opinion covered the meaning units: ‘Process of Care’, ‘Interpersonal Relation- ship’, ‘Perspectives of burned patients’, ‘Process of Work Organization’ and ‘Suggestions for Change’. The study showed the complexity of meeting the individual burnt, being necessary to the multidisciplinary team values the opinion of this patient in order to provide assistance with the greatest impact on improving his or her quality of life.